Perancangan Media Pembelajaran Perakitan Komputer Berbasis Android untuk Meningkatkan Kemampuan Kognitif Siswa - Shutan Fitrah Arthadi; Ita Fitriati; Ahyar, Ahyar (Inventor: Jurnal Inovasi dan Tren Pendidikan Teknologi Informasi, 2023)
This study aims to design android-based computer assembly learning media and determine the feasibility of android-based computer assembly learning media. The end result of this research is Android-Based Computer Assembling Learning Media to Improve Students' Cognitive Abilities that have been tested for feasibility. This study uses the R&D method with the waterfall model. The stages in this study include five stages, namely (1) the requirements stage (needs analysis), (2) design, (3) coding (writing program code), (4) Testing (product testing). ), and (5) maintenance (product maintenance). Based on the final assessment of the material experts with a percentage of 82.5% stated that the android-based computer assembly learning media that had been developed was declared feasible. Meanwhile, the final result of the assessment of small group respondents on Android-based computer assembly learning media with a percentage of 89.1% was stated to be Very Feasible. The final result of the large group respondent's assessment of the android-based computer assembly learning media with a percentage of 88.7% was stated to be Very Feasible. Based on the results of the analysis of the average percentage (%) pre-test and post-test results involving 30 students who were taken randomly consisting of 3 classes (X TKJ 1, X TKJ 2 and X TKJ 3) to get a percentage of 96.7% included in Very Good category. Abstrak Penelitian ini bertujuan untuk merancang media pembelajaran perakitan komputer berbasis android dan mengetahui tingkat kelayakan media pemebalajaran perakitan komputer berbasis android. Hasil akhir dari penelitian ini adalah media pembelajaran perakitan komputer berbasis android untuk meningkatkan kemampuan kognitif siswa yang telah teruji kelayakannya. Penelitian ini menggunakan metode R&D dengan model waterfall Tahapan dalam penelitian ini meliputi lima tahapan, yaitu (1) tahap requirement (analisis kebutuhan), (2) design, (3) coding (penulisan kode program), (4) Testing (uji coba produk), dan (5) maintenance (pemeliharaan produk). Berdasarkan penilaian akhir dari Ahli materi dengan persentase 82,5% menyatakan bahwa media pembelajaran perakitan komputer berbasis android yang telah dikembangkan dinyatakan Layak. Sedangkan hasil akhir dari penilaian responden kelompok kecil terhadap media pembelajaran perakitan komputer berbasis android dengan persentase 89,1% dinyatakan Sangat Layak. Hasil akhir dari penilaian responden kelompok besar terhadap media pembelajaran perakitan komputer berbasis android dengan persentase 88,7% dinyatakan Sangat Layak. Berdasarkan hasil analisis rerata persentase (%) hasil pre-test dan post-test yang melibatkan 30 siswa yang diambil secara acak yang terdiri dari 3 kelas (X TKJ 1, X TKJ 2 dan X TKJ 3) mendapatkan persentase 96,7% termasuk dalam kategori Sangat Baik.